PRACTICAL FACTORS OF EDUCATING YOUNG STUDENTS IN A SPIRIT OF PATRIOTICISM IN MUSIC LESSONS. (Universal International Scientific Journal, 2026)
This article analyzes the practical factors of educating students in the spirit of patriotism in music lessons. In particular, the issues of forming feelings of love for the Motherland, national pride and loyalty in students through the study of national melodies and songs, patriotic works and the State Anthem of Uzbekistan are highlighted. Also, the effectiveness of practical performance activities, stage performances and the use of modern pedagogical technologies in the lesson process is revealed. The article considers ways to ensure the spiritual and moral development of young people through music education and educate them as well-rounded individuals.
Keywords: music education, patriotic education, national values, musical culture, performing activities, aesthetic education, youth education